AUTHORITY AND RESPONSIBILITY OF A NOTARY PUBLIC IN MAKING FIDUCIARY DEED OF GUARANTEE AT RURAL CREDIT BANKS (A STUDY AT TJANDRA ARTHA LESTARI BANK, BANDAR LAMPUNG) - Oddy Marsa JP (Universitas Lampung, 2019)
Notary status is regulated in Act Number 2 of 2014 relative to Amendments to Act Number 30 of 2004 (hereinafter referred to as UUJN). In carrying out its authority, the Notary is obliged to provide investment guarantees and is obliged to fulfill the rights and obligations of the parties in economic cooperation and other matters needed. This study uses a normative legal approach, which uses secondary data as primary data, consisting of primary, secondary and tertiary legal material. This study aims to analyze the authority and responsibility of a notary public in issuing fiduciary deeds to banks and their legal consequences if a fiduciary guarantee is made by the notary is not registered at the fiduciary registration office. The results of the research and discussion resulted that a notary must be very careful in carrying out all his duties and authority over the rights and obligations of the parties and in the results of this study also showed that the role and responsibilities of the notary public in making a fiduciary deed at the bank financial institution because it was legal liability, namely the guarantee of legal certainty over a fiduciary deed made / registered. The legal consequence of PT Tjandra Artha Lestari if it is not registered is that the fidusian recipient will experience difficulties if the fiduciary provider defaults and the fidusian recipient does not have the right to overtake other creditors in terms of paying off debts.